Paleoseismology of the 2016 MW 6.1 Petermann earthquake source: Implications for intraplate earthquake behaviour and the geomorphic longevity of bedrock fault scarps in a low strain‐rate cratonic region. Issue 7 (3rd May 2021) - King, Tamarah Rosellen; Quigley, Mark; Clark, Dan; Zondervan, Albert; May, Jan‐Hendrik; Alimanovic, Abaz
Abstract: The 20 May 2016 M W 6.1 Petermann earthquake in central Australia generated a 21 km surface rupture with 0.1 to 1 m vertical displacements across a low‐relief landscape. No paleo‐scarps or potentially analogous topographic features are evident in pre‐earthquake Worldview‐1 and Worldview‐2 satellite data. Two excavations across the surface rupture expose near‐surface fault geometry and mixed aeolian‐sheetwash sediment faulted only in the 2016 earthquake. A 10.6 ± 0.4 ka optically stimulated luminescence (OSL) age of sheetwash sediment provides a minimum estimate for the period of quiescence prior to 2016 rupture. Seven cosmogenic beryllium‐10 ( 10 Be) bedrock erosion rates are derived for samples < 5 km distance from the surface rupture on the hanging‐wall and foot‐wall, and three from samples 19 to 50 km from the surface rupture. No distinction is found between fault proximal rates (1.3 ± 0.1 to 2.6 ± 0.2 m Myr −1 ) and distal samples (1.4 ± 0.1 to 2.3 ± 0.2 m Myr −1 ). The thickness of rock fragments (2–5 cm) coseismically displaced in the Petermann earthquake perturbs the steady‐state bedrock erosion rate by only 1 to 3%, less than the erosion rate uncertainty estimated for each sample (7–12%). Using 10 Be erosion rates and scarp height measurements we estimate approximately 0.5 to 1 Myr of differential erosion is required to return to pre‐earthquake topography. By inference any pre‐2016 fault‐related topography likely required a similar time for removal. We conclude that the Petermann earthquake was the first on this fault in the last ca. 0.5–1 Myr. Extrapolating single nuclide erosion rates across this timescale introduces large uncertainties, and we cannot resolve whether 2016 represents the first ever surface rupture on this fault, or a > 1 Myr interseismic period. Either option reinforces the importance of including distributed earthquake sources in fault displacement and seismic hazard analyses. Abstract : Multi‐methods approach to quantify Quaternary rupture history of the 2016 M W 6.1 Petermann earthquake fault source in central Australia. No geographic or trench evidence for prior rupture, and cosmogenic beryllium‐10 ( 10 Be) erosion rates suggest no analogous ruptures have occurred on this fault since 0.5 to > 1 Ma. Results suggest > 0.5–1 Myr interseismic period or that the 2016 earthquake was the first surface rupture to occur on this fault.